Meta-Sintesis Blended Learning dan Flipped Classroom dalam Pembelajaran Bahasa Arab: Desain, Implementasi, dan Efektivitas - Julham Hukom (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
Blended learning (BL) and flipped classroom (FC) represent two hybrid instructional models that structurally integrate face-to-face with digital components. In the context of Arabic language instruction, both models promise a balance between the depth of grammatical learning supported by direct teacher interaction and digital flexibility supporting independent practice. However, comprehensive synthesis of how BL and FC are designed, implemented, and produce impact in the specific context of Arabic language remains limited. This meta-synthesis aims to integrate findings from empirical studies on BL and FC in Arabic language learning to produce a more holistic understanding. A systematic search was conducted across Scopus, Web of Science, ERIC, and Google Scholar for the period 2019–2025. Of 231 articles identified, 20 studies met the inclusion criteria. Using Noblit and Hare’s (1988) meta-ethnographic approach, analysis yielded four main synthetic themes: (1) design characteristics of effective BL and FC in Arabic language contexts; (2) factors influencing implementation success across geographic contexts; (3) differential effects of BL and FC on Arabic language skills and academic achievement; and (4) structural challenges and contextual recommendations. The synthesis produces the Arabic Hybrid Implementation Framework (AHIF) as a design guide for BL/FC sensitive to the linguistic characteristics of Arabic and Islamic educational contexts.